(untitled) (África, 2007)
Since its inception, the field of ethnomusicology has dramatically changed. In the past fifty years of its existence in the United States of America, ethnomusicology has been defined and redefined in order to shed light and clarify on its ultimate goal- objective—raison d’être. It is not an exaggeration to assert that over the years, as a socio-humanity discipline, ethnomusicologists are gradually becoming aware of their mission—to contribute to the understanding of human being—rather than limit their activities to the understanding of the mechanisms of their subject—study of music for its own sake. To accomplish this mission, ethnomusicologists have heavily relied on the interdisciplinary nature of their objectives. In the process, ethnomusicologists have been selectively borrowing theories and research models from their sister disciplines, such as sociology, anthropology, ethnography, and linguistics, in order to configure their own paradigm. The present essay is devoted to the mise au point (to clarify, to bring into focus) of the definition of ethnomusicology and the re-interpretation of the borrowed theories and methodologies as they are applied to the quest of the ultimate goal –the truth– in the field of ethnomusicology.